The soil organic carbon and its role on climate change - Burbano Orjuela, Hernán (Revista de Ciencias Agrícolas, 2018)
Climate change, one of the most important global challenges, is an unavoidable problem for society. Soil, among other alternatives, can play a role mitigating the detrimental effects of CO2-driven climate change. In this article, I discuss soil’s potential to store carbon in the context of the carbon cycle and its possible role on the modulation of climate change. Finally, I explain a global initiative of soil management as an approach to mitigate climate change.